Du lecteur automate aux émotions universelles - Guillaume Pinson (Contextes)
This article proposes some reflections on a history of "the affective life of the past" (Lucien Febvre), taking an interest in emotions in the literary and cultural history of the Nineteenth Century press. How did the reader express sensitivities, certain anxieties, emotions and desires, closely related to the consumption of the newspaper ? Following synthetic and methodological proposals, the article focuses on the intimate and emotional appropriations of the newspaper in a series of sources, notably in the novel. From the reader immersed in his reading to the great "universal emotions" of the mass newspaper, we explore some of these bodily, emotional and social reactions. Emotional life in a media context brings together "the interior" (the affected reader’s body) and "the outside" (the social body moved), which leads us to propose that the "civilization of the newspaper" has given rise to a profound remodeling of sensibilities since the Nineteenth century, and that emotions have played an important role in the history of communication.